(untitled) (Journal of Asian Development Studies, 2024)
Pakistan faces challenges in balancing language policy, instructional practices, and sociocultural diversity to compete with the world. With over 7000 languages globally, Pakistan only focuses on two languages: one national language, i.e. Urdu and then the official language, English. This research aims to analyze the impact of multilingual education on students’ academic performance, particularly for students in Pakistan, and its implications for future career directions. This research uses Cummins’ Multilingual Education Framework as the theoretical lens in examining 40 participants, who are university students and teachers. The results demonstrate the importance of the ongoing advocacy for languages and suggested policies for effective MLE. Additional Chinese, German, Russian, and French languages are also shown to further career opportunities. Findings also reveal that 80% of the participants favored MultiLanguage Education as it is essential for career development and professional growth. The study also showed that multilingual education could improve students’ cognitive skills, social interactions, and economic growth. Further, this research helps the emergence of multilingual education in Pakistan, which meets the needs of dual and multilingual students living in the globalized world.